LA GEOGRAFÍA: APORTES AL DESARROLLO SOSTENIBLE - Place, Susan E. (2011)
La geografía se plantea como  la disciplina mejor capacitada para construir un enfoque de desarrollo menos destructivo, más social y sostenible. Este  artículo promueve una mejor  comprensión del valor de  la perspectiva geográﬁca  al desarrollo sostenible. La Geografía como puente entre  las ciencias naturales y  sociales permite que veamos el paisaje como producto de la interacción del ser humano con el ambiente. La   geografía como disciplina cientíﬁca facilita la construcción de un desarrollo sostenible. Palabras claves: desarrollo sostenible, ecología política, cartografía participativa, SIG de Participación Pública, ecoturismo, historia de pensamiento geográﬁco.AbstractGeography establishes  itself as a better capacity discipline  in order  to build a  less destructive, more social and sustainable development focus. This article promotes a better understanding of the value of perspective geography to sustainable development. Geography as a bridge between the natural and social sciences permits us to see the landscape as a product of the interaction between man and the environment. Geography is a scientiﬁc discipline that facilitates construction of sustainable development.Key Words: sustainable development, political ecology, participative cartography, Geography Information System of public participation, ecotourism, history of geographic thinking.